Molybdenum-doped iridium-based multicomponent alloy core-shell structure PEM water electrolysis catalyst and preparation method thereof
Through the PEM electrolytic water catalyst doped with molybdenum, the problems of high catalyst cost and low corrosion resistance in the prior art are solved, and cheap, efficient and stable electrolytic water catalytic effect is achieved.
Patent Information
- Application Number
- CN202510279541.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-11
AI Technical Summary
The existing PEM electrolytic catalyst has high cost and low corrosion resistance, making it difficult to achieve both cheap, efficient and stable.
The PEM electrolytic water catalyst is used to form the core-shell structure of the iridium-based multi-alloy core-shell structure of the iridium-cobalt core and the iridium shell, and disperse the transition metal molybdenum between the shell and the core, combining one-step synthesis method and selective etching method to improve the stability and activity of the catalyst.
The catalyst is cheap, efficient and stable, the content of the precious metal iridium is reduced, the catalytic activity and corrosion resistance of electrolytic water is improved, the electrode response rate is fast, the electrochemical impedance is small, and the electrochemical activity area is large.
Smart Images

Figure CN119776899A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of proton exchange membrane water electrolysis catalysts, in particular to a molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst and a preparation method thereof. Background Art
[0002] In order to cope with the continuous depletion of traditional fossil energy and serious environmental pollution problems, it is urgent to develop green new energy. Hydrogen energy, as an efficient and clean secondary energy source, has received widespread attention. However, the main way to produce hydrogen is still fossil fuels, which goes against the original intention of reducing traditional energy consumption. Therefore, it is necessary to develop green hydrogen production technology based on water electrolysis. In recent years, PEM water electrolysis (proton exchange membrane water electrolysis) hydrogen production technology has developed rapidly and is an effective way to prepare green hydrogen, but its high cost and low corrosion resistance limit their large-scale commercial application. An important reason is that the cost of catalysts in membrane electrodes is too high, mainly precious metals such as platinum and iridium; and due to the strong acid environment, general metals are difficult to work stably for a long time. Many scientific researchers have tried to develop non-precious metal catalysts and their derivatives, but without the protection of platinum and iridium, such catalysts are difficult to resist the inherent corrosion and oxidation sensitivity problems in the process of water electrolysis. Therefore, the development of cheap, efficient and stable low-precious metal electrode materials is the key to realizing the large-scale application of PEM water electrolysis hydrogen production.
[0003] Research in recent years has shown that the stability and activity of catalysts can be improved and the content of precious metals can be reduced by adjusting the chemical composition and nanostructure of the catalysts. The chemical composition of the catalyst can be adjusted by doping transition metals (including Ni, Co, etc.). This method can not only reduce the content of precious metals and achieve the purpose of reducing costs, but also improve the electrocatalytic activity, because different metals will produce a synergistic effect and increase the active sites. The nanostructure of the catalyst can be adjusted by forming a core-shell structure, a hollow structure, a single atom, a cluster structure, etc. So far, most of the research on iridium-based multi-catalysts can only meet one or two of the three factors of cheapness, high efficiency, and stability, but there is no better way to balance the three. Summary of the invention
[0004] In order to overcome the defects in the above-mentioned prior art, the present invention provides a molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst, in which transition metals molybdenum and cobalt are composited with precious metal iridium to form a special core-shell structure electrocatalyst, which has the characteristics of low cost, high efficiency and stability.
[0005] To achieve the above object, the present invention adopts the following technical solutions, including: The invention discloses a molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst, wherein the catalyst is a nano-spherical core-shell structure electrocatalyst; wherein the shell of the spherical core-shell structure is iridium, the core is iridium-cobalt, and the transition metal molybdenum is dispersed between the shell and the core.
[0006] The present invention also provides a method for preparing a molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst, comprising the following steps: S1, taking iridium source, cobalt source, molybdenum source, surfactant, alcohol reducing agent and stabilizer into a beaker and mixing them thoroughly, and ultrasonically cleaning them in an ultrasonic cleaner for a set time, then moving them into a constant temperature water bath and stirring them on a magnetic stirrer to make all the raw materials basically dissolved, moving the sample obtained after stirring into an oil bath for heat preservation, and obtaining a solution with precipitation after cooling; S2, centrifugally purify the solution with precipitate obtained in step S1 N times, N>1, to obtain a precipitate as the catalyst, marked as Mo x -IrCo y @Ir.
[0007] Preferably, the method further comprises the following steps: S3, dispersing the precipitate obtained in step S2 in an etching solution, and after etching for a set time, obtaining an etched mixed solution; S4, centrifugally purify the mixed solution after etching obtained in step S3 M times, M>1, and obtain the precipitate after etching as the catalyst, marked as Mo x -IrCo y @Ir-Etch.
[0008] Preferably, in step S1, the iridium source is selected from one of iridium acetylacetonate or iridium chloride; the cobalt source is selected from one of cobalt acetylacetonate or cobalt chloride; the molybdenum source is selected from molybdenum acetylacetonate; the surfactant is one of hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide; the stabilizer is oleylamine; and the alcohol reducing agent is 1,2-hexadecanediol.
[0009] Preferably, in step S1, the ultrasonic time is 10 min; and the temperature of the water bath is 70-80°C.
[0010] Preferably, in step S1, stirring is performed using a magnetic stirrer, the rotation speed of the magnetic stirrer is 1000 rpm, and the stirring time is 10 min; the insulation temperature of the oil bath pot is 260-270° C., the insulation time is 40-60 min, and the heat transfer oil is dimethyl silicone oil.
[0011] Preferably, in step S1, the molar ratio of the iridium source to the molybdenum / cobalt source is 0.5:0.6, and the molar ratio of the cobalt source to the molybdenum source is 1:2, 1:1, 2:1 or 1:0.
[0012] Preferably, in step S2, a set amount of toluene and a set amount of methanol / anhydrous ethanol are added for the centrifugal purification, and the solution ratio is 1:2; each centrifugal purification time is 5 minutes; the first centrifugal speed is 10000 rpm, and the centrifugal speed each time thereafter is 8000 rpm.
[0013] Preferably, in step S3, the etching solution is cerium nitrate and copper nitrate; the concentration ratio of cerium to copper in the etching solution is 0:1, 1:3, 1:2, 1:1, 2:1, 3:1 or 1:0; and the etching time is 3, 6, 9, 12, 18 or 24 hours.
[0014] Preferably, in step S4, the centrifugal solution is 10 mL of anhydrous ethanol, the centrifugal purification time is 5 min each time, the first centrifugal speed is 10000 rpm, and the centrifugal speed is 8000 rpm each time thereafter.
[0015] The advantages of the present invention are: (1) The present invention combines transition metals with noble metals to form a special core-shell structure electrocatalyst, which is an important method for saving costs, improving efficiency and stability, and has great scientific research potential and industrial prospects.
[0016] (2) The present invention utilizes cheap and abundant transition metals molybdenum and cobalt as partial substitutes for the current commercial precious metal iridium catalyst, thereby solving the problem of high cost of PEM water electrolysis catalyst and further improving the catalytic activity and stability of water electrolysis.
[0017] (3) The molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst prepared by the present invention has good corrosion resistance due to the doping of transition metal molybdenum in the PEM water electrolysis hydrogen production process, thereby improving the corrosion resistance and stability of the catalyst.
[0018] (4) The present invention adopts a one-step synthesis method combined with a selective etching method. Although different metals may produce synergistic effects during the synthesis process, they may also produce phenomena such as uneven agglomeration. After selective etching, excess metal clusters and uneven degradation are removed, so that the stability is further improved. In a long-term test of 100 hours, the voltage rise is less than 1%, and it has good stability.
[0019] (5) The present invention uses the prepared molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst instead of the commercial iridium oxide catalyst as the anode material for PEM water electrolysis to produce hydrogen, and its current density reaches 10mA / m2 The required voltage overpotential is only 206 mV, which is better than the commercial iridium oxide catalyst (272 mV). The electrode has a fast response rate, small electrochemical impedance, and a large electrochemical active area, which significantly improves the catalytic activity of the oxygen evolution reaction.
[0020] (6) The present invention uses the prepared molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst to replace the commercial iridium oxide catalyst as the anode material for PEM water electrolysis to produce hydrogen. Due to the doping of transition metals cobalt and molybdenum, the content of precious metal iridium is significantly reduced, and the content of iridium per unit area is about 0.1 mg / cm 2 , which is much lower than the iridium content in commercial electrolytic cells (2-4 mg / cm 2 ), which greatly reduces the cost of the catalyst.
[0021] (7) The preparation method of the present invention can also achieve large-scale preparation of materials by changing the content of each metal source, which is easy to realize industrialization and has important engineering application value for promoting the large-scale application of PEM water electrolysis to produce hydrogen.
[0022] (8) The catalyst prepared by the method of the present invention has high OER (oxygen evolution reaction) activity and good stability. It is also low in cost and easy to industrialize. It solves the shortcomings of the existing PEM water electrolysis hydrogen production and has important value in the field of electrochemical applications and practical engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 @TEM image of Ir-Etch.
[0024] Figure 2 Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 HRTEM image of @Ir-Etch.
[0025] Figure 3 Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 HAADF-STEM image and elemental mapping by @Ir-Etch.
[0026] Figure 4 Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 @Ir-Etch's EDX spectrum.
[0027] Figure 5 Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02@XRD pattern of Ir-Etch.
[0028] Figure 6 Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 XPS spectrum of @Ir-Etch.
[0029] Figure 7 Oxygen evolution polarization curves of the catalysts prepared in Examples 1 to 17 of the present invention and the comparative catalyst IrO2.
[0030] Figure 8 Mo prepared in Examples 1, 16 and 17 of the present invention 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir and IrCo 0.06 @Ir's Tafel slope curve.
[0031] Fig. 9 Mo prepared in Examples 1, 16 and 17 of the present invention 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir and IrCo 0.06 Electrochemical impedance curve of @Ir.
[0032] Fig.10 Mo prepared in Examples 1, 16 and 17 of the present invention 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir and IrCo 0.06 @Ir CV curves and double-layer capacitance diagrams corresponding to different scan rates.
[0033] Fig.11 Mo prepared in Examples 1, 16 and 17 of the present invention 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir and IrCo 0.06 Stability curve of @Ir on glassy carbon electrode.
[0034] Fig.12 Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 Long-term stability curve of @Ir-Etch on carbon paper electrode.
[0035] Fig.13 It is a schematic diagram of the catalyst preparation process of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] A molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst is a nano-spherical core-shell structure electrocatalyst; wherein the shell of the spherical core-shell structure is iridium, the core is iridium-cobalt, and the transition metal molybdenum is dispersed between the shell and the core.
[0038] Furthermore, a portion of the redundant metal clusters can be removed by selective etching.
[0039] Example 1 like Fig.13 As shown, the preparation method of the molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst comprises the following steps: S1, weigh 10.3 mg of 1,2-hexadecanediol (alcohol reducing agent), 32 mg of hexadecyltrimethylammonium chloride (surfactant), 5.2 mg of acetylacetonate cobalt (cobalt source), 24.5 mg of acetylacetonate iridium (iridium source) with a balance, measure 5 mL of oleylamine solution (stabilizer) with a measuring cylinder, and place all of them in a 25 mL heat-resistant beaker for mixing. Then, weigh 13.1 mg of acetylacetonate molybdenum (molybdenum source), the molar ratio of the cobalt source to the molybdenum source in this embodiment 1 is 1:2, quickly pour it into the above mixture, ultrasonicate it with an ultrasonic cleaner for about 10 minutes, then move the beaker into a water bath of about 80 ° C and stir it at a constant temperature on a magnetic stirrer for 10 minutes, and adjust the speed of the magnetic stirrer to 1000 rpm to mix the raw materials evenly, and the solution is light yellow at this time. Finally, transfer the beaker to an oil bath that has been preheated to 270 ° C, take it out after keeping warm for 1 hour, and wait for it to cool naturally to room temperature to obtain a black solution with precipitation.
[0040] S2, pour the obtained black solution with precipitate into a 50mL centrifuge tube, measure 5mL toluene and 10mL methanol and pour them into the centrifuge tube to mix, and centrifuge at 10000rpm for 5min. After taking it out, pour out the supernatant to obtain a black precipitate. To further purify the precipitate, pour in 5mL toluene and 10mL anhydrous ethanol and mix them, and centrifuge at 8000rpm for 5min. After taking it out, pour out the supernatant, repeat the above steps several times, and the centrifugation speed is 8000rpm each time, until the supernatant is colorless and transparent. Finally, put the black precipitate after centrifugation purification into a vacuum drying oven at 60℃ and dry it for 6h to obtain the dried black precipitate, which is marked as Mo. 0.04 -IrCo 0.02 @Ir.
[0041] S3, the prepared Mo 0.04 -IrCo 0.02 Pour @Ir into 1 mL of anhydrous ethanol, and use an ultrasonic cleaner to sonicate for 10 min to completely disperse it in the solution, which is recorded as solution A. In addition, weigh 2.172 g of cerium nitrate and 0.938 g of copper nitrate (the concentration ratio of cerium nitrate to copper nitrate is 1:1) and dissolve them in 5 mL of deionized water, and stir them with a magnetic stirrer at 1000 rpm for about 5 min to obtain solution B. Pour solution A into solution B, use an ultrasonic cleaner to sonicate for 10 min to completely disperse solution A in solution B, and let it stand at room temperature for 6 h to obtain a mixed solution after standing.
[0042] S4, pour the mixed solution after standing into a 50mL centrifuge tube, measure 10mL of anhydrous ethanol and pour it into the centrifuge tube, centrifuge at 10000rpm for 5min, take out and pour out the supernatant to obtain a black precipitate. To further purify the precipitate, pour in 10mL of anhydrous ethanol and centrifuge at 8000rpm for 5min, take out and pour out the supernatant, repeat the above steps several times, and the centrifugation speed is 8000rpm each time, until the supernatant is colorless and transparent. Finally, put the black precipitate after centrifugation purification into a vacuum drying oven at 60℃ and dry it for 6h to obtain a dried black precipitate, marked as Mo. 0.04 -IrCo 0.02 @Ir-Etch.
[0043] The Mo obtained in step S4 0.04 -IrCo 0.02 @Ir-Etch is a molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst prepared in Example 1 of the present invention.
[0044] Example 2 The difference from Example 1 is that in step S1, the amounts of cobalt acetylacetonate and molybdenum acetylacetonate are changed to 7.8 mg and 9.8 mg, that is, the molar ratio of the cobalt source to the molybdenum source is changed to 1:1, and the rest is the same as Example 1.
[0045] Example 3 The difference from Example 1 is that in step S1, the amounts of cobalt acetylacetonate and molybdenum acetylacetonate are changed to 10.4 mg and 6.6 mg, that is, the molar ratio of the cobalt source to the molybdenum source is changed to 2:1, and the rest is the same as Example 1.
[0046] Example 4 The difference from Example 1 is that in step S1, the amounts of cobalt acetylacetonate and molybdenum acetylacetonate are changed to 15.6 mg and 0 mg, that is, only the cobalt source is added without the molybdenum source, and the rest is the same as Example 1.
[0047] Example 5 The difference from Example 1 is that in step S3, the amounts of cerium nitrate and copper nitrate are changed to 1.086 g and 1.407 g, that is, the concentration ratio of cerium nitrate to copper nitrate is changed to 1:3, and the rest is the same as Example 1.
[0048] Example 6 The difference from Example 1 is that in step S3, the amounts of cerium nitrate and copper nitrate are changed to 3.25 g and 0.469 g, that is, the concentration ratio of cerium nitrate to copper nitrate is changed to 3:1, and the rest is the same as Example 1.
[0049] Example 7 The difference from Example 1 is that in step S3, the amounts of cerium nitrate and copper nitrate are changed to 1.447 g and 1.251 g, that is, the concentration ratio of cerium nitrate to copper nitrate is changed to 1:2, and the rest is the same as Example 1.
[0050] Example 8 The difference from Example 1 is that in step S3, the amounts of cerium nitrate and copper nitrate are changed to 2.893 g and 0.626 g, that is, the concentration ratio of cerium nitrate to copper nitrate is changed to 2:1, and the rest is the same as Example 1.
[0051] Example 9 The difference from Example 1 is that in step S3, the amounts of cerium nitrate and copper nitrate are changed to 4.34 g and 0 g, that is, the concentration ratio of cerium nitrate to copper nitrate is changed to 1:0, and the rest is the same as Example 1.
[0052] Example 10 The difference from Example 1 is that in step S3, the amounts of cerium nitrate and copper nitrate are changed to 0 g and 1.88 g, that is, the concentration ratio of cerium nitrate to copper nitrate is changed to 0:1, and the rest is the same as Example 1.
[0053] Embodiment 11 The difference from Example 1 is that in step S3, the mixture is allowed to stand at room temperature for 3 hours, and the rest is the same as Example 1.
[0054] Example 12 The difference from Example 1 is that in step S3, the mixture is allowed to stand at room temperature for 9 hours, and the rest is the same as Example 1.
[0055] Example 13 The difference from Example 1 is that in step S3, the mixture is allowed to stand at room temperature for 12 hours, and the rest is the same as Example 1.
[0056] Embodiment 14 The difference from Example 1 is that in step S3, the mixture is allowed to stand at room temperature for 18 hours, and the rest is the same as Example 1.
[0057] Embodiment 15 The difference from Example 1 is that in step S3, the mixture is allowed to stand at room temperature for 24 h, and the rest is the same as Example 1.
[0058] Example 16 The difference from Example 1 is that step S3 and step S4 are not performed, and the rest are the same as Example 1. 0.04 -IrCo 0.02 @Ir is the molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst prepared in Example 16 of the present invention.
[0059] Embodiment 17 The difference from Example 4 is that step S3 and step S4 are not performed, and the rest are the same as Example 4. The dried black precipitate obtained in step S2 is marked as IrCo 0.06 @Ir, will IrCo 0.06 @Ir is the molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst prepared in Example 17 of the present invention.
[0060] The catalyst prepared in the above example was subjected to physical characterization test, and the test results are as follows: Figure 1 Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 @TEM image (transmission electron microscope image) of Ir-Etch. Figure 1 It can be observed that the Mo prepared by combining the one-step synthesis method (i.e., steps S1-S2) and the selective etching method (i.e., steps S3-S4) 0.04 -IrCo 0.02@Ir-Etch, the catalyst has a nano-spherical structure and the overall surface has petal-like protrusions. This morphology can expose more active sites and improve catalytic activity.
[0061] Figure 2 The Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 @Ir-Etch HRTEM image (high resolution transmission electron microscope image). Figure 2 It can be observed that the diameter of the nanospheres is about 30-50 nm and the lattice spacing is about 0.21 nm.
[0062] Figure 3 The Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 @Ir-Etch's HAADF-STEM image (scanning transmission image) and elemental mapping (elemental mapping includes line scan and surface scan). Figure 3 Among them, (a) is a HAADF-STEM image, (b) is an elemental surface scan of a mixture of Ir, Co, and Mo, (c) is an elemental line scan of a mixture of Ir, Co, and Mo, and (d), (e), and (f) are elemental surface scans of Ir, Co, and Mo, respectively. Figure 3 It can be observed that the catalyst presents an IrCo alloy core, which is protected by an Ir-rich shell, and the molybdenum element is evenly distributed in the IrCo core and the Ir-rich shell; the thickness of the shell is about 5 to 10 nm.
[0063] Figure 4 The Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 @Ir-Etch EDX spectrum. Figure 4 It can be observed that the element energy of Ir in the catalyst is the most obvious, followed by Co, while the characteristic peak of Mo is relatively weak.
[0064] Figure 5 The Mo prepared in Example 1 of the present invention 0.04 -IrCo 0.02 @Ir-Etch's XRD pattern (X-ray diffraction pattern). Figure 5 It can be observed that the lattice spacings of Ir, Co, and Mo are 0.222nm (Ir, JCPDS: 00-006-0598), 0.205nm (Co, JCPDS: 00-015-0806), and 0.233nm (Mo, JCPDS: 01-088-2331), respectively. The lattice spacing of multi-component composite catalysts is generally between the maximum spacing and the minimum spacing of single elements. Therefore, Mo 0.04 -IrCo0.02 @Ir-Etch's lattice spacing should be 0.205~0.233nm, Figure 2 (HRTEM image) is consistent with the measured lattice spacing of 0.21nm.
[0065] Figure 6 Mo prepared in Examples 1, 16 and 17 of the present invention 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir, IrCo 0.06 @Ir XPS spectra (X-ray photoelectron spectrum) of each element, Figure 6 In the figure, (a) is the overall spectrum, (b), (c), and (d) are the specific narrow spectra of the three elements Ir, Co, and Mo, respectively. Since different elements will produce diffraction peaks at different horizontal coordinate positions under the test, and the diffraction peaks of each element have different valence states, the valence state composition and element content of each element in the catalyst can be determined through peak fitting. Figure 6 It can be observed that there are three elements, Ir, Co, and Mo. Ir mainly exists in 0 and 4 valence states, Co mainly exists in 0, 2, and 3 valence states, and Mo mainly exists in 0, 5, and 6 valence states. In addition, as etching occurs, Mo 0.04 -IrCo 0.02 The characteristic peak area of Ir in @Ir-Etch did not change significantly, while the characteristic peak areas of Co and Mo decreased significantly, indicating that etching only removed excess Co and Mo.
[0066] The electrochemical performance of the catalyst prepared in the above example was tested, and the test results are as follows: The present invention adopts a three-electrode system to carry out electrochemical performance testing, and evaluates the performance change of the oxygen evolution reaction in the electrolysis of water to produce hydrogen. The three-electrode system is divided into a working electrode, a counter electrode and a reference electrode, wherein the catalyst electrode is the working electrode, the platinum wire electrode is the counter electrode, the saturated silver chloride electrode is the reference electrode, and the electrolyte is a 0.5M H2SO4 solution.
[0067] The test conditions of the present invention are as follows: Test temperature: room temperature (25-28°C); Linear scanning voltage range: 1.197~1.597V (relative to reversible hydrogen electrode); Linear scan rate: 5mv / s; Electrochemical impedance voltage: 1.5 V (relative to reversible hydrogen electrode); Frequency range of impedance test: 10 5 ~0.01Hz; CV cycle voltage range: 0.9~1.0V (relative to reversible hydrogen electrode); Scan rate of CV test: 5, 10, 20, 40, 60, 80, 100 mv / s; Constant current density for stability test: 10mA / cm 2 .
[0068] The preparation method of the working electrode in the present invention is as follows: first, 5 mg of the prepared catalyst is added into 1 mL of anhydrous ethanol, and ultrasonicated for 20 minutes to form a fully mixed suspension.
[0069] (1) Glassy carbon electrode: Use a pipette to measure 5 μL of the suspension and drop it on a glassy carbon electrode with a diameter of 3 mm. After drying at room temperature for 10 to 15 min, repeat the above steps once. Use a pipette to measure 5 μL of 0.2 wt% Nafion solution and drop it on the glassy carbon electrode. Dry it at room temperature and set aside for use.
[0070] At the same time, commercial IrO2 was used as a comparative catalyst and a control working electrode was prepared according to the above method.
[0071] It is worth noting that, except for the long-term stability test, the glassy carbon electrode was used as the test electrode (working electrode).
[0072] (2) Carbon paper electrode: Cut into 1×1 cm 2 The carbon paper was placed in acetone, anhydrous ethanol, and deionized water for 10 minutes each, and then placed in a drying oven at 60°C for 2 hours before use. 143 μL of the suspension and 71.5 μL of 0.2 wt% Nafion solution were measured with a pipette, and after thorough mixing, 54 μL of the mixed solution was dropped on a 1×1 cm 2 Place the sample on a carbon paper electrode, dry it in a drying oven at 60°C for 5 to 10 minutes, repeat the above steps 3 times; finally, place it in a drying oven at 60°C and dry it for 6 hours before use.
[0073] Figure 7 is the oxygen evolution polarization curve of the catalysts prepared in all embodiments of the present invention and the comparative catalyst IrO2, Figure 7 In the figure, (a) shows the oxygen evolution polarization curves of Examples 1 to 9, and (b) shows the oxygen evolution polarization curves of Examples 10 to 17 and the comparative catalyst IrO2. The overpotentials corresponding to each catalyst are shown in Table 1. It can be seen that: the current density is 10 mA / cm 2 When the Mo prepared in Example 1 0.04 -IrCo 0.02 @Ir-Etch has the best oxygen evolution catalytic activity with an overpotential of only 206mV.
[0074] Table 1 Overpotentials corresponding to various catalysts ; Figure 8 Mo prepared in Examples 1, 16, and 17 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir, IrCo 0.06 Tafel slope curve of @Ir. Figure 8 It can be observed that Mo 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir, IrCo 0.06 The Tafel slopes of @Ir are 59.7mV / dec, 61.5mV / dec, and 69.8mV / dec, respectively. 0.04 -IrCo 0.02 @Ir-Etch has the smallest Tafel slope, indicating that its electrode response rate is the fastest.
[0075] Fig. 9 Mo prepared in Examples 1, 16, and 17 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir, IrCo 0.06 @Ir electrochemical impedance curve. Fig. 9 It can be observed that Mo 0.04 -IrCo 0.02 @Ir-Etch has the smallest semicircle diameter, indicating that its electrochemical impedance value is the smallest.
[0076] Fig.10 Mo prepared in Examples 1, 16, and 17 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir, IrCo 0.06 @Ir's CV curve and double-layer capacitance diagram. Fig.10 In the figure, (a), (b), and (c) are Mo 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir, IrCo 0.06 @Ir CV curve, (d) is the double layer capacitance diagram. Fig.10 It can be observed that Mo 0.04 -IrCo0.02 @Ir-Etch has the largest double-layer capacitance, indicating that its electrochemically active area is the largest.
[0077] Fig.11 Mo prepared in Examples 1, 16, and 17 0.04 -IrCo 0.02 @Ir-Etch, Mo 0.04 -IrCo 0.02 @Ir, IrCo 0.06 @Ir stability curve. Fig.11 It can be observed that after 20 hours of testing, Mo 0.04 -IrCo 0.02 @Ir-Etch voltage rise (about 1.1%)<Mo 0.04 -IrCo 0.02 @Ir voltage rise (about 2.8%)<IrCo 0.06 The increase in @Ir voltage (about 3.7%) proves that the doping of Mo element and chemical etching both play a certain role in improving the stability of the catalyst.
[0078] Fig.12 The Mo prepared in Example 1 0.04 -IrCo 0.02 @Ir-Etch long-term stability curve on carbon paper electrode. Fig.12 It can be observed that after 100h of long-term testing, Mo 0.04 -IrCo 0.02 @Ir-Etch voltage rise is less than 1%, showing the good stability of the catalyst.
[0079] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst, characterized in that: The catalyst is a nano-spherical core-shell structure electrocatalyst; wherein the shell of the spherical core-shell structure is iridium, the core is iridium-cobalt, and the transition metal molybdenum is dispersed between the shell and the core.
2. A method for preparing a molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst, characterized in that: The following steps are involved: S1, taking iridium source, cobalt source, molybdenum source, surfactant, alcohol reducing agent and stabilizer into a beaker and mixing them thoroughly, and ultrasonically cleaning them in an ultrasonic cleaner for a set time, then moving them into a constant temperature water bath and stirring them on a magnetic stirrer to dissolve the raw materials, moving the sample obtained after stirring into an oil bath for heat preservation, and obtaining a solution with a precipitate after cooling; S2, centrifugally purify the solution with precipitate obtained in step S1 N times, N>1, to obtain a precipitate as the catalyst according to claim 1, marked as Mo x -IrCo y @Ir.
3. The method for preparing the platinum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst according to claim 2, characterized in that: The following steps are also included: S3, dispersing the precipitate obtained in step S2 in an etching solution, and after etching for a set time, obtaining an etched mixed solution; S4, centrifugally purify the mixed solution after etching obtained in step S3 M times, M>1, and obtain the precipitate after etching as the catalyst according to claim 1, marked as Mo x -IrCo y @Ir-Etch.
4. The method for preparing the platinum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst according to claim 2, characterized in that: In step S1, the iridium source is selected from one of iridium acetylacetonate and iridium chloride; the cobalt source is selected from one of cobalt acetylacetonate and cobalt chloride; the molybdenum source is selected from molybdenum acetylacetonate; the surfactant is one of hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium bromide; the stabilizer is oleylamine; and the alcohol reducing agent is 1,2-hexadecanediol.
5. The method for preparing the platinum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst according to claim 2, characterized in that: In step S1, the ultrasonic time is 10 minutes; the temperature of the water bath is 70-80°C.
6. The method for preparing the platinum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst according to claim 2, characterized in that: In step S1, a magnetic stirrer is used for stirring, the rotation speed of the magnetic stirrer is 1000 rpm, and the stirring time is 10 minutes; the insulation temperature of the oil bath pot is 260-270° C., the insulation time is 40-60 minutes, and the heat transfer oil is dimethyl silicone oil.
7. The method for preparing the platinum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst according to claim 2, characterized in that: In step S1, the molar ratio of the iridium source to the molybdenum / cobalt source is 0.5:0.6, and the molar ratio of the cobalt source to the molybdenum source is 1:2, 1:1, 2:1 or 1:
0.
8. The method for preparing the platinum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst according to claim 2, characterized in that: In step S2, a set amount of toluene and a set amount of methanol / anhydrous ethanol are added for the centrifugal purification, and the solution ratio is 1:2; each centrifugal purification time is 5 minutes; the first centrifugal speed is 10000 rpm, and the subsequent centrifugal speed is 8000 rpm.
9. The method for preparing the platinum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst according to claim 3, characterized in that: In step S3, the etching solution is cerium nitrate and copper nitrate; the concentration ratio of cerium to copper in the etching solution is 0:1, 1:3, 1:2, 1:1, 2:1, 3:1 or 1:0; and the etching time is 3, 6, 9, 12, 18 or 24 hours.
10. The method for preparing the molybdenum-doped iridium-based multi-element alloy core-shell structure PEM water electrolysis catalyst according to claim 3, characterized in that: In step S4, the centrifugal solution is 10 mL of anhydrous ethanol, the centrifugal purification time is 5 min each time, the first centrifugal speed is 10000 rpm, and the centrifugal speed is 8000 rpm each time thereafter.
Citation Information
Patent Citations
Preparation method of N-doped porous carbon coated nano-particles of Co-Ir core-shell structure and application of N-doped porous carbon coated nano-particles of Co-Ir core-shell structure to catalytic water splitting
CN108048866A
Ir-coated IrOx core-shell catalyst as well as preparation method and application thereof
CN116516399A
IrNi alloy nanocage complete water splitting catalyst as well as preparation method and application of IrNi alloy nanocage complete water splitting catalyst
CN117344343A
Method for improving acidic oxygen evolution reaction performance of iridium-based electrocatalyst based on molybdenum doping strategy
CN118957675A
Diamond-core-shell metal composite catalyst, preparation method and electrolytic cell
CN119020816A
Cited By
Graphene composite iridium-based ternary alloy PEM electrolyzed water catalyst and preparation method thereof
CN121023562A
Graphene composite iridium-based ternary alloy pem electrolysis water catalyst and preparation method thereof
CN121023562B